Enhancing public acceptance towards waste-to-energy incineration projects: Lessons learned from a case study in China. (July 2019) - Liu, Yong; Ge, Yujia; Xia, Bo; Cui, Caiyun; Jiang, Xiaoyan; Skitmore, Martin
Highlights: Strategies respond to the NIMBY syndrome in the WTE industry is explored using case study. The traditional DAD decision-making approach is the root cause of NIMBY syndrome. Strategies with transparency and democracy can effectively promote public acceptance. The results provide a clear connection between theoretical research and industry practice. Abstract: Waste-to-energy incineration provides an effective solution for efficient and effective municipal solid waste (MSW) disposal, and plays an important role in the regional circular economy and sustainable urban development. However, waste-to-energy incinerations face considerably strong opposition from the local community globally because of the potential hazards to environment and health. This paper conducts a comprehensive case study of the Yuhang Jiufeng waste-to-energy plant in Zhejiang province, which is regarded as first waste-to-energy incineration project to truly overcome such an issue in China. The results reveal that the traditional technical-based, closed Decide-Announce-Defend decision-making approach is the root cause of public opposition, and a more open and democratic publicly involved approach played an important role in the successful re-decision-making of the Jiufeng plant. Meanwhile, a series of response strategies, such as compensation and risk communication, can effectively promote the local residents' public acceptance through improvements in their benefit/risk perceptions and public trust. The findings of this study will add new knowledge to the current understanding of public opposition, and benefit both governments and waste-to-energy professionals by paving the way to enhancing public acceptance of waste-to-energy incineration facilities.